2021
DOI: 10.3389/fmed.2021.779627
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Base Excess and Mortality Among Patients in ICU With Acute Kidney Injury

Abstract: Objective: This study aimed to explore the association between base excess (BE) and the risk of 30-day mortality among patients with acute kidney injury (AKI) in the intensive care unit (ICU).Methods: This retrospective study included patients with AKI from the Medical Information Mart for Intensive Care (MIMIC)-IV database. We used a multivariate Cox proportional-hazards model to obtain the hazard ratio (HR) for the risk of 30-day mortality among patients with AKI. Furthermore, we utilized a Cox proportional-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…For each, we fitted a univariable logistic spline regression modeling the logit of AKI. Natural restricted cubic splines with two degrees of freedom were used as nonlinear relations between AKI and frequently reported risk factors (25)(26)(27)(28)(29)(30).…”
Section: Pipeline Of Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…For each, we fitted a univariable logistic spline regression modeling the logit of AKI. Natural restricted cubic splines with two degrees of freedom were used as nonlinear relations between AKI and frequently reported risk factors (25)(26)(27)(28)(29)(30).…”
Section: Pipeline Of Analysesmentioning
confidence: 99%
“…They also displayed a higher recovery rate (HR = 1.6 for AKI recovery, 95% CI [1.0; 2.7], p = 0.05, Figure 3B). In addition, patients from cluster 3 also displayed a distinct metabolic profile, expressing the impaired metabolism profile at a higher rate (35% (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) vs. 27% (22-31) p = 0.04, Figure 3C), and had a higher hospital mortality (55% vs. 20% (11-29) p < 0.001, Figure 3D). Finally, only patients from cluster 3 exhibit a significant positive association between AKI severity and risk of hospital mortality (Figure 3E).…”
Section: Clinical Characteristics and Outcomes Of The Three Aki Pheno...mentioning
confidence: 99%
“…In addition, several other studies have also explored the relationships between metabolic acidosis and clinical outcomes of AKI patients. Cheng Y et al [ 29 ] found a U-shaped association between base excess value measured at the ICU admission and 30 day all-cause mortality in critically AKI patients, and both lower (≤ − 3 mEq/L)and higher (≥ 9 mEq/L) base excess would increase the risk of 30 day all-cause mortality. One latest study by Uusalo and colleagues [ 30 ] acknowledged that for perioperative AKI patients requiring CRRT, blood lactate at ICU admission and CRRT initiation were both independently associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Using these pre-processed data, we fitted the relation between AKI and each potential predictor in a univariable fashion, using a logistic regression. As nonlinear relations between AKI and risk factors have often been reported [25][26][27][28][29][30] we also fitted a logistic regression using natural restricted cubic splines with two degrees of freedom.…”
Section: Explicative Statistical Modelmentioning
confidence: 99%
“…Patients from clusters 1 and 2 also showed a distinct metabolic profile compared to cluster 3, expressing the impaired metabolism profile at a lower rate (22% [19][20][21][22][23][24] versus 29% [23][24][25][26][27][28][29][30][31][32][33] p=0.005, Figure 3d).…”
Section: Renal Endpointsmentioning
confidence: 99%